The Influence of Financial Sector Growth, Dependency Ratio, and Education Level on the Penetration of Sharia Life Insurance in Indonesia - Yustia Dewi; Marliyah; Muhammad Ikhsan Harahap (Fakultas Ekonomika dan Bisnis Universitas 17 Agustus 1945 Semarang, 2026)
Indonesia has the largest Muslim population in the world, yet its sharia life insurance penetration lags far behind other ASEAN countries such as Malaysia and Thailand. This phenomenon warrants further investigation, given the substantial untapped market potential. This study aims to analyze the influence of financial sector growth, dependency ratio, and education level on sharia life insurance penetration in Indonesia. It employs the Theory of Insurance Demand proposed by Beck and Webb (2003) as the theoretical foundation, which posits that economic, demographic, and social factors collectively shape insurance demand. The research adopts a quantitative approach using multiple linear regression analysis. The data consist of 112 monthly secondary observations from January 2014 to April 2023, obtained from OJK and BPS through documentation techniques. The results show that all three variables have a positive and significant effect on sharia life insurance penetration, both partially and simultaneously, with an explanatory power of 61.1 percent of the variation. These findings confirm that economic, demographic, and educational factors serve as important determinants in driving the future penetration of sharia life insurance in Indonesia.